Calibration Analysis Of Seepage Flow At Arch Dam Foundation – A Case Study - Stevcho Mitovski, Ljupcho Petkovski, Frosina Panovska (Macedonian association for geotechnics, 2022)
The assessment of the structural stability and the behavior of the dam during construction and service period is of vital importance. In the paper are presented acknowledgments from the calibration analysis of the seepage process in the foundation of an concrete arch dam, by application of numerical methods, based on Finite Element Method (FEM), with applied code SOFiSTiK. The aim of the task is to assess and predict the seepage process, that includes calibration (based on monitoring data) and prognosis stage (short-term and long-term) focusing on variable such as seepage flow. Seepage analysis in time domain was carried out the for calibration and prognosis stage. The key conclusion from the numerical experiment is that obtained seepage flow values within the calibration stage are matching good with the measured data, that allows to predict the future seepage flow data and to assess the state of the foundation and permissible boundary values.
Keywords: Seepage flow; FEM; Rock foundation, Calibration Process; Prediction.